OPTIMIZATION OF CRITICAL-CURRENT DENSITY OF BULK YBCO SUPERCONDUCTOR PREPARED BY COPRECIPITATION IN OXALIC-ACID - KIM, DJ; KROEGER, DM (CHAPMAN HALL LTD, 1993)
YBa2Cu3O7-x (YBCO) superconductor powder was prepared from mixtures of solutions containing yttrium, barium, and copper nitrates by coprecipitation in oxalic acid. Single-phase YBCO was obtained from a solution mixture of 14 vol % excess of barium nitrate and 12 vol % excess of copper nitrate relative to the stoichiometry of YBCO. The optimal pH in the coprecipitation process was determined to be 6.6-6.7 which was obtained by using 12 vol % excess oxalic acid anhydrous solution of the required oxalic acid to convert all metal cations to oxalates and adding a dilute ammonium hydroxide solution. The measurement of critical current density, J(c), of bulk YBCO prepared by the coprecipitation, showed a trend that the J(c) increased together with the degree of orthorhombic distortion of YBCO phase which depended on the sample density and the content of impurity phases.
Keywords: TRANSPORT CRITICAL CURRENT; YBA2CU3OX SUPERCONDUCTORS; OXIDE SUPERCONDUCTORS; GRAIN-BOUNDARIES; Y1BA2CU3OX; POWDER; SIZE; BA2YCU3O7-X; TEMPERATURE; SAMPLES